Experimental Study of Heat Pipe for Solar Collector Heater - Wahyu, Dian (Jurnal Teknik Mesin (JTM), 2016)
Heat pipes with a size of 0.0127 m diameter x 1.3 m lenght x 0.0008 m thick and absorber with a size of 1m length x 0.1 m width has been created and tested to be used as a solar collector heating element. Heat pipes are made using water as the heat transport medium and using a stainless steel mesh wick 120 as a tool that helps accelerate the flow of condensate inside the heat pipe. Testing of heat pipes will be do in two condition at an inclination of 30o , before the heat pipes selected as the heating element in the solar collector. Testing of heat pipe on the first condition is done by using 1,000 ml of hot water temperature of 100oC with the power supply of 20 watts as a heat source in the evaporator side and further testing of pipe heat was tested by direct solar radiation, this test is intended to see directly if heat pipe was made able to work in conditions that are expected. Tests are done to see the heat transfer capacity and response speed (τ) of the heat pipe. Based on testing obtained the fastest response in the heat pipes transfer of the heat contained in the filling ratio of 20% with the heat transfer efficiency of 75%.